Efficacy of different extenders on sperm characteristics and lipid peroxidation during liquid storage of boar semen - ASHWANI KUMAR SINGH; GURSHER SINGH SIDHU; AMARJEET BISLA; AJEET KUMAR; MRIGANK HONPARKHE (Indian Journal of Animal Sciences)
The present study was aimed to test and evaluate the efficacy of six different extenders, Modena, Beltsville thawing solution (BTS), glucose sodium salt of EDTA-potassium sodium tartrate-sodium citrate (GEPS), Safe Cell, Androstar Plus (ASP) and M III on boar sperm parameters and lipid peroxidation during preservation. Sixty ejaculates were collected from six breeding Large White Yorkshire boars and preserved at 17°C for 120 h. Each ejaculate was evaluated for motility, viability, hypo-osmotic swelling test (HOST), acrosome integrity, in vitro capacitation/acrosome reaction and lipid peroxidation based on malonaldehyde (MDA) levels at 0, 24, 48, 72, 96 and 120 h of storage. The percentage of motile and viable spermatozoa, HOS-positive sperm population, intact acrosomes and in vitro capacitated/acrosome-reacted spermatozoa declined significantly from 0-120 h of preservation in all extenders. BTS and Modena extenders preserved higher sperm motility and viability from 24-120 h and acrosome integrity from 48-120 h of storage in comparison to remaining extenders. BTS maintained highest proportion of HOS-positive sperm at 96 h and 120 h and in vitro acrosome reaction percentage at 120 h of preservation among all extenders. From 24-120 h of storage, the MDA concentrations were lower in semen preserved in BTS and Modena than the other extenders. Thus, it can be concluded that both BTS and Modena were more effective among the tested extenders for preservation of boar semen at 17°C.